Logistiskstudie av ett flissystem med 74 tons flisekipage - Spånberg, Kristoffer (2016)
The purpose of this report is to investigate the problems and time wasters for a system with two 74-ton chips carriages which is a chipper and a truck. This is achieved through a time study with focus on logistics and each operation has been noted. The study pointed to long industrial times for the transport vehicle. The reason was the unloading mechanism that had a slowly unload and also generated more short transports in industry. The conclusion is that the short transport distances required high availability to the chipper, while at longer distances needs high load capacity. Primarily, it is the process of chipping that cost and therefore it is important that the chipper has as high utilization rate as possible.